PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DISPERINDAGKOP DAN UMKM MANOKWARI - Octavia Nataria; Selmi Dedi; Margareth Sylvia Sabarofek (Cakrawala Management Business Journal, 2018)
This study aims to determine whether work stress and workload partially and simultaneously influence the performance of employees of the Industry and Trade Office of Cooperatives and SMEs in Manokwari Regency. The type of research used is associative research with quantitative methods. This study uses saturated samples with a total sample of 49 employees. The analytical tool used is multiple linear regression, F test and t test. The results of this study indicate partially that work stress does not affect performance. The results of the t test on the workload affect the performance. Simultaneously shows that work stress and workload simultaneously have a significant effect on performance.